THE RELATIONSHIP BETWEEN SOCIAL MEDIA USE AND SLEEP DISORDERS IN ADOLESCENTS - Muhammad Muflih Maulidan; Mutia Avila Vellani; Ikram Maulana; Azzahra Puti Adama; Fuller, M.Hum (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
This study analyzes the relationship between social media use and sleep disorders among adolescents in Indonesia. Through a meta-analysis approach of three main studies, this study examined the causal mechanisms, predisposing factors, and health implications of social media dependence. The results showed a consistent significant association between social media intensity and decreased sleep quality in adolescents, with an average of 69.3% being active users and 65.3% experiencing poor sleep quality. Statistical analysis revealed a strong correlation (coefficient of 0.646) and a significant relationship (p-value <0.001). These findings underscore the urgency of digital health education and structured interventions to reduce the negative impact of social media on adolescent sleep health.